Efficacy of autologous micrografts technology: a promising approach for chronic wound healing and tissue regeneration—a pilot study - Baglioni, Elisabetta Adelaide; Perego, Franco; Paolin, Elisa; Abate, Alberto; Pusceddu, Tommaso; Zavan, Barbara; Bocchiotti, Maria Alessandra (Frontiers in Medicine, 2024)
Introduction This study explores the efficacy of Autologous Micrografts Technology (AMG) in treating chronic wounds refractory to traditional therapies. Methods AMGs, derived from adipose tissue or dermis using a mechanical fragmentation process, were applied to patients with post-surgical dehiscence. A comprehensive evaluation of wound healing outcomes, including surface area reduction and complete healing, was conducted over a 90-day follow-up period. Additionally, the study investigated the cellular antioxidant activity of AMG solutions and characterized the exosomes obtained through mechanical disaggregation. Results Results indicate significant improvements (p < 0.05) in wound healing, with 91.66% of patients showing at least a 50% reduction in lesion size and 75% achieving complete healing by day 90. Notably, AMG technology demonstrated immediate efficacy with fat-only application, while combined dermis and fat micrografts showed longer-term benefits, particularly in chronic wounds. The study also elucidated the mechanism of action of AMGs, highlighting their role in enhancing cellular antioxidant activity and exosome-mediated tissue regeneration. Discussion Overall, these findings underscore the promising potential of AMG technology as a versatile and effective treatment option for chronic wounds, warranting further investigation into its mechanisms and clinical applications.